2016
DOI: 10.7759/cureus.721
|View full text |Cite
|
Sign up to set email alerts
|

Irritable Bowel Syndrome: A Global Challenge Among Medical Students

Abstract: Irritable bowel syndrome (IBS) has been identified as one of the more highly prevalent and costly gastrointestinal disorders. Despite its uncertain etiology, risk factors, such as stress and academic load, are well correlated with the prevalence of the disease. Being in one of the most stressful and challenging environments, medical students are predisposed to have high rates of IBS. The socioeconomic burden of the disease on its sufferers is devastating as their quality of life is reduced, mandating additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 33 publications
5
42
0
1
Order By: Relevance
“…51 Many researchers have stated that medical students have significant amounts of stress throughout their years of university life. 52,53 The results of this study revealed that many students eat because of negative emotions like feeling lonely (44.7%), nervous (42.1%), or bored (51.1%). Conversely, others sometimes eat due to feeling happy (56.6%).…”
Section: Discussionmentioning
confidence: 82%
“…51 Many researchers have stated that medical students have significant amounts of stress throughout their years of university life. 52,53 The results of this study revealed that many students eat because of negative emotions like feeling lonely (44.7%), nervous (42.1%), or bored (51.1%). Conversely, others sometimes eat due to feeling happy (56.6%).…”
Section: Discussionmentioning
confidence: 82%
“…Irritable bowel syndrome (IBS) is a gastrointestinal disorder, characterized by altered bowel habits with abdominal discomfort or pain with the absence of organic pathology. IBS is a highly prevalent disorder that has a great impact on patients' quality of life [21]. In this work, we aimed to study the frequency of IBS in the selected study sample and to find out the associated factors related to this illness.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rome IV criteria, the diagnostic criteria for Irritable bowel syndrome is defined as recurrent abdominal pain on average at least 1 day/week in the last 3 months, associated with 2 or more of the following:related to defecation, associated with a change in frequency or form (appearance) of stool [ 16 ]. IBS is a chronic biopsychological disorder which has complex symptoms appearing as altered bowel habits without organic pathology[ 17 ]. As we know, IBS is so common that it affects nearly 10–20% of adolescents and adults in western societies and is also the frequentest cause of children with recurrent abdominal pain [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%